OBSERVATIONS ON 'THE EQUITY METHOD' AND INTERCORPORATE RELATIONSHIPS. - Dickerson, W. E.; Jones, J. Weldon (The Accounting Review, 1933)
Abstract This article presents information on the equity method and intercorporate relationships. In a series of articles on "Intercorporate Relationships" appearing in the journal "American Accountant" from April-July 1982, economist Lewis A. Carman presented the "equity method" for preparing consolidated balance sheets. The equity method eliminates the necessity of making all adjustments, which are solely and entirely between the investment accounts and the surplus accounts. Consolidation on a cost basis is complex and is subject to errors, which are not patent. Hence, the usual procedure involved in this method is, to adjust the investment account for changes in net worth since date of acquisition. The equity method does not invalidate the computation of goodwill on the conventional basis that is the excess of cost over book value at date of acquisition. Either total or partial goodwill may be set up on the work sheet. The equity method does not introduce algebra except where intercorporate relationships are exceedingly complex.